STABILITAS KADAR KAROTENOID EKSTRAK BUAH PANDAN (Pandanus tectorius) PADA CAHAYA DAN SUHU PENYIMPANAN - Aryayustama, Made Gabhina; Wartini, Ni Made; Suwariani, Ni Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 6 No 3 (2018): SeptemberDO - 10.24843/JRMA.2018.v06.i03.p05, 2018)
Carotenoid extract of pandanus fruit has some deficiencies that are easily damaged by acid, light, and high temperatures. The aim of this study was to know the best treatment of light and temperature to maintain the stability of the pandanus fruit extract during storage. The experiment in this study used Completely Randomized Design with two factors. The first factor was light that consisted of two levels: dark and bright. The second factor was storage temperature that consisted of three levels: 4±3?C, 28±3?C and 45±3?C. The results showed that the treatment of 4±3?C in dark condition had the best treatment to maintain the stability of pandanus fruit extract with the smallest decrease of carotenoid 13,47% during 4 weeks of storage. Keywords : Pandanus fruit extract, carotenoids, light, temperature, stability